Territorial Marketing Impacts on Foreign Direct Investment Attraction(Empirical Evidence in Nghe An Province, Vietnam) - Dang Thanh Cuong; Banh Thi Thao; Trinh Thi Hang; Hoang Thi Viet; Thi Ngoc Han Doan (Cogent Economics & Finance, 2023)
FDI and territorial marketing are fields of interest and research by many scientists and managers. However, this is still a new field of science in Vietnam, both academically and practically. The awareness of building a local image to investors, especially foreign investors, is still limited. This has had a significant impact on attracting FDI into many provinces of Vietnam in general and Nghe An province in particular. Although Nghe An has issued and implemented many policies to attract FDI, FDI attraction results are not commensurate with the potential and position of the province. In this study, the author conducted a survey of foreign investors who made surveys to invest in or implemented FDI projects in Nghe An. Data is primary data which is collected from 160 foreign investors who invested or did investing survey, then processed by exploratory factor analysis (EFA) and multiple regression to determine the territorial marketing factors affecting the investment decisions of foreign direct investors in Nghe An. Research results have shown that 6 territorial marketing factors have a positive impact on the investment decision of foreign direct investors, this will be an important foundation to propose solutions for territorial marketing to attract FDI in Nghe An in the next coming time.
Keywords: E22; E28; F00; G00; 330; FDI attraction; territorial location; Territorial marketing; territorial price; territorial product